2020
DOI: 10.1037/apl0000453
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and outcomes of workplace ostracism: A meta-analysis.

Abstract: Researchers have shown great interest in the antecedents and outcomes of workplace ostracism, which has led to an expansive body of research. In light of this work, the current article fulfills the need for a comprehensive review and meta-analysis of the antecedents and outcomes associated with workplace ostracism. We begin our review by adapting a victimization perspective to understand ostracism as a triadic social process between the victim, perpetrator, and the environment. The meta-analytic results then s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
358
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(376 citation statements)
references
References 154 publications
13
358
1
4
Order By: Relevance
“…Employees, especially high self‐monitors, can take actions to alter their social acceptance among others and thus break the negative spiral of workplace ostracism. For research into workplace ostracism specifically, our findings highlight that employees can take actions to influence others and reshape the social environment to reduce their ostracism experiences; a conventional approach instead conceptualizes workplace ostracism as a static, negative condition and mainly investigates ways to manage its impact (Howard et al ., 2020). More broadly, being ostracized evokes behaviours designed to regain social acceptance, but our study adds new insights to prior research by empirically demonstrating that favour rendering can help ostracized people, if they are high self‐monitors, regain social acceptance (i.e., enhanced popularity) and reduce their ostracism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Employees, especially high self‐monitors, can take actions to alter their social acceptance among others and thus break the negative spiral of workplace ostracism. For research into workplace ostracism specifically, our findings highlight that employees can take actions to influence others and reshape the social environment to reduce their ostracism experiences; a conventional approach instead conceptualizes workplace ostracism as a static, negative condition and mainly investigates ways to manage its impact (Howard et al ., 2020). More broadly, being ostracized evokes behaviours designed to regain social acceptance, but our study adds new insights to prior research by empirically demonstrating that favour rendering can help ostracized people, if they are high self‐monitors, regain social acceptance (i.e., enhanced popularity) and reduce their ostracism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies already have established that people with less fear of negative evaluations (Maner et al ., 2007) or higher rejection sensitivity (Romero‐Canyas et al ., 2010) are more likely to use impression management tactics. Yet the results of a meta‐analytic review of workplace ostracism research (Howard et al, 2020) indicate a negative association between workplace ostracism and helping behaviours, suggesting that people tend not to help others after being ostracized. Balliet and Ferris (2013) argue that whether ostracized employees help others reflect a social dilemma; they cannot distance themselves from others if they realize helping others might enhance their social acceptance in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found that psychological well-being is associated with higher employee satisfaction, better performance, better relationships with teammates, less stress and more personal development (Lomas et al, 2017). Moreover, well-being (or lack thereof) have been studied in relation to workplace ostracism (Howard, Cogswell, & Smith, 2020), work stress (Bliese, Edwards, & Sonnentag, 2017), organizational citizenship behavior (Davila & Finkelstein, 2013), and interpersonal conflict (Wickham, Williamson, Beard, Kobayshi, & Hirst, 2016).…”
Section: Conflict Behaviors In South Koreamentioning
confidence: 99%